Prenatal assistance in the private health sector: a reading on demedicalization (Research, Society and Development, 2020)
This study aims to analyze, from the perspective of de-medicalization, prenatal care in the private health sector. It is an integrative review with search for data between August and October 2019 in the Medline / PubMed, Web of Science, Editora Elsevier reference base, Nursing Database and Scientific Electronic Library Online. 15 articles were selected as the final sample for data analysis. It was identified that the private network offers easier access, facilities, a greater number of consultations, but an excessive performance of exams. Thus, it appears from this scenario that there is a medicalization of health care, marked by the excessive use of technology and decision-making power by health professionals. In view of this, it is concluded that demedicalization is incipient in prenatal care in the private health network. Thus, it is necessary to reflect on the decision-making role of women in the sense of powerful provocations to contribute to the reorganization of the way of health care in the private sector.